"We would be dead in the water without our social media!": Women using entrepreneurial bricolage to mitigate drought impacts in rural Australia. Issue 2 (15th March 2022) - Casey, Sarah; Crimmins, Gail; Rodriguez Castro, Laura; Holliday, Penny
ABSTRACT: It is widely understood that climate change transforms rural communities' economic activities that have historically relied on farming through off-farm income for economic stability and mitigation. Entrepreneurship has become a central feature of the diversification of rural labor, but there is still a need to document how rural women operationalize entrepreneurship in their communities. We use three narrative interviews to examine how settler farming women in the Murweh and Paroo Shires of outback Queensland in Australia have mitigated the devastating financial impact of the most recent drought through the lens of entrepreneurial bricolage for off-farm income. The findings, generated through grounded theory, highlight the complexity of entrepreneurial bricolage processes through women's use of networking (digital and communal), learning digital technologies, repurposing of resources and places, and use of family labor. The paper contributes theoretically to place-based, gendered and context-specific understandings of drought mitigation, through identifying how entrepreneurial bricolage is employed.